ASSESSING THE EFFECTIVENESS OF DIFFERENT TRADITIONAL PROCESSING METHODS ON PROXIMATE COMPOSITION OF FRESHWATER CATFISH, MYSTUS NGASEP - NANAOBI, HEMAM; SAROJNALINI, CHUNGKHAM; DANIEL, N.; Romharsha, Hawaibam (Journal of the Inland Fisheries Society of India, 2026)
The aim of this study was to evaluate the effectiveness of three different traditional processing methods (steaming, smoking and frying) on proximate composition of the freshwater catfish, Mystus ngasep. A standard AOAC protocol was adapted to analyze the following proximate parameters in fish: moisture, crude protein, crude lipids and total ash. The results show that all three traditional processing methods had significantly (p